1977
DOI: 10.1002/ajpa.1330460302
|View full text |Cite
|
Sign up to set email alerts
|

Genes and people in the caspian littoral: A population genetic study in northern Iran

Abstract: Data for the distribution of alleles controlling two blood group systems and secretor status, for hemoglobin types, five serum protein groups and 15 red cell enzyme systems has been obtained. Eleven of the systems showed polymorphic variation and these systems have been used to calculate genetic distances using Morton's Kinship measure. No systematic relationship between genetic distance and geographic location of linguistic affiliation is apparent. There is, however, an apparent cline of decreasing frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
2

Year Published

1978
1978
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 20 publications
2
27
2
Order By: Relevance
“…Besides the common three phenotypes, some variant type PGM 6-1, was present in the Isfahan Iranians. Similar type of variant was found in the Caspian littoral area (Kirk et al, 1977).…”
Section: B Phosphoglucomutase Locus I (Pgm1)supporting
confidence: 78%
See 3 more Smart Citations
“…Besides the common three phenotypes, some variant type PGM 6-1, was present in the Isfahan Iranians. Similar type of variant was found in the Caspian littoral area (Kirk et al, 1977).…”
Section: B Phosphoglucomutase Locus I (Pgm1)supporting
confidence: 78%
“…A single case of s-MDH 5-1 have been found in the Caspian (Kirk et al, 1977). However, all of the samples in the present series showed the normal type.…”
Section: G Malate Dehydrogenase (Mdh)contrasting
confidence: 53%
See 2 more Smart Citations
“…Other studies identified the role of suspected aetiological factors (Pour and Ghadirian, 1974;Hormozdiari et al, 1975;IARC, 1975;Kirk et al, 1976;Joint Iran-IARC Study Group, 1977;Hewer et al, 1978;Mahboubi and Aramesh, 1980;Cook-Mozaffari et al, 1979;Farhud et al, 1979;Hashemi et al, 1979;O'Neill et al 1980;Kmet et al, 1981) showing the highest risk to be among the traditionally semi-nomadic Turkoman population. There also seemed to be an association with a very restricted diet from infancy (low in animal protein and fruit or vegetables), consumption of dry, coarse bread contaminated with sharp seeds and silica fibres and of hot tea, and the regular smoking or swallowing of opium dross ('sukhtheh') which was shown to be mutagenic (Hewer et al, 1978;Dowlatshahi and Miller, 1985).…”
mentioning
confidence: 99%